2015
DOI: 10.3892/ol.2015.3325
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of immune cell subsets in relapsed, thymoma-associated minimal change disease: A case report

Abstract: Abstract. The most frequently described glomerulopathy in patients with thymoma is minimal change disease (MCD). The present study reports the case of a 63-year-old female with recurrent thymoma and poorly-controlled paraneoplastic MCD, who was enrolled on a phase I/II clinical trial (no. NCT01100944) and treated with the histone deacetylase inhibitor, belinostat, in combination with cisplatin, doxorubicin and cyclophosphamide. Treatment resulted in a complete radiological response, a dramatic reduction in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…Autoreactive T cell clones escaping negative selection in the abnormal thymic tissue or suppression of regulatory T‐cells controlling self‐tolerance are likely integral in development of thymoma‐associated autoimmune disease and may have contributed to serum AA production in this case . Minimal change disease, a glomerulopathy associated with nephrotic syndrome, was described in an older woman with recurrent thymoma . Interestingly, when her thymoma was treated and her proteinuria decreased, her Th17/regulatory T cell ratio decreased .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Autoreactive T cell clones escaping negative selection in the abnormal thymic tissue or suppression of regulatory T‐cells controlling self‐tolerance are likely integral in development of thymoma‐associated autoimmune disease and may have contributed to serum AA production in this case . Minimal change disease, a glomerulopathy associated with nephrotic syndrome, was described in an older woman with recurrent thymoma . Interestingly, when her thymoma was treated and her proteinuria decreased, her Th17/regulatory T cell ratio decreased .…”
Section: Discussionmentioning
confidence: 86%
“…6,15 Minimal change disease, a glomerulopathy associated with nephrotic syndrome, was described in an older woman with recurrent thymoma. 16 Interestingly, when her thymoma was treated and her proteinuria decreased, her Th17/regulatory T cell ratio decreased. 16 We propose that a combination of thymoma associated and immune dysregulation and tumoral inflammation may have resulted in renal amyloid deposition in this dog.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we feel it is reasonable to consider that abnormalities in the immune system may result from thymoma as well as thymectomy, since the thymus is the primary stromal milieu guiding the maturation and selection of T-lymphocytes ( 15 , 16 ). Interestingly, a detailed description of changes in the immune cell subset composition in recurrent thymoma-associated MCD was recently published ( 17 ), implying the presence of immunologic disturbance in subjects with recurrent disease. However, whether or not different histological types of thymoma result in distinct paraneoplastic glomerular injuries remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the effect of chemotherapy in patients with relapsed thymoma was investigated based on the measurement of the T cell subsets in a patient with minimal change disease (MCD) ( 16 ). The study found that Th17 cells decreased and that proteinuria resolved after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%